Pertinence des reformes LMD au Cameroun : analyses des qualités personnelles et professionnelles des diplômés employés dans les entreprises formelles - Joseph Bomda; Innocent Fozing; Vandelin Mgbwa (Éducation et Socialisation)
The present contribution deals with the appreciation of the personal and professional qualities of graduate employees in the era of the LMD reforms by their direct supervisors in formal public and private enterprises in Cameroon. Drawing on the fields of intervention of occupational psychosociology and organisations, ten indicators of the personal and professional qualities of an employee was cross-referenced with the graduating institutions (polytechnics and public and private universities). Following multiple imputation of missing values, the test of homogeneity of variances (Box Test) led them to the use of the non-parametric Kruskal-Wallis H test. The results reveal a differentiated assessment of the personal and professional qualities of employed graduates according to the graduating institutions. Direct supervisors find polytechnicians better equipped than academics, as it was already the case before the LMD reforms. As it stands, these results reveal a vagueness that detracts from the political rhetoric on the professionalization of academics in the LMD reform period, on the one hand, and the new world order in education marked by a process of standardization that ignores particularities, on the other.